2022
DOI: 10.1002/alz.12677
|View full text |Cite
|
Sign up to set email alerts
|

Modifying effects of race and ethnicity and APOE on the association of physical activity with risk of Alzheimer's disease and related dementias

Abstract: IntroductionWe investigated whether the protective association of physical activity with risk of Alzheimer's disease and related dementias (ADRD) has genetic or behavioral variations.MethodsIn the Multiethnic Cohort, we analyzed moderate or vigorous physical activity (MVPA) reported at ages 45 to 75 among 88,047 participants in relation to 13,039 incident diagnoses of late‐onset ADRD identified in Medicare claims (1999 to 2014), by five racial and ethnic groups, hours sitting, and in a subset (16%), apolipopro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Therefore, the two optimal exposures may jointly interact with dementia related genetic risk. Emerging evidence confirmed that a higher frequency of participation in physical activity can improve handgrip strength and increase vitamin D level, and the interaction between physical and APOE genotype have been reported [ 44 , 45 ]. Brain structural alteration may be another potential mechanism.…”
Section: Discussionmentioning
confidence: 93%
“…Therefore, the two optimal exposures may jointly interact with dementia related genetic risk. Emerging evidence confirmed that a higher frequency of participation in physical activity can improve handgrip strength and increase vitamin D level, and the interaction between physical and APOE genotype have been reported [ 44 , 45 ]. Brain structural alteration may be another potential mechanism.…”
Section: Discussionmentioning
confidence: 93%
“…The risk of developing AD is influenced by heritable factors to the extent of 60–80% ( Mez et al, 2016 ; Bao et al, 2022 ; Karlsson et al, 2022 ), and more than 40 genetic risk loci associated with AD have been identified ( Kunkle et al, 2019 ; Sullivan et al, 2022 ; Dato et al, 2023 ; Fominykh et al, 2023 ; Huang et al, 2023 ; Wainberg et al, 2023 ). Among these loci, apolipoprotein E (APOE) alleles exhibit the strongest association with the disease ( Park et al, 2023 ; Polsinelli et al, 2023 ; Sadleir and Vassar, 2023 ). Advanced biomarkers, such as positron emission tomography (PET) scans and plasma assays for aβ and phosphorylated tau, demonstrate significant potential for both clinical and research applications ( Feinkohl et al, 2020 ; Peng et al, 2021 ; Shen et al, 2022 ; Wilson et al, 2022 ; Gonzalez-Ortiz et al, 2023 ; Zhang et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%